IMPLEMENTASI LESSON STUDY : PENERAPAN PEMBELAJARAN KONTEKSTUAL DALAM MATERI PERPINDAHAN KALOR SECARA KONDUKSI PADA SISWA KELAS 6 SD - Duden Saepuzaman; Suparman Suparman; Endi Suhendi; Setya Utari; Muhamad Gina Nugraha (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2014)
This research‟s purposes are to describe the implementation of Contextual learning in heat conduction concept. Based on class teacher, several student still confuse to describe the heat conduction procces if the learning heat conduction just given to the student, not given the real world phenomen ini the class. Ini research, the implementation of lesson study following steps, plan, doo and see. Teacher‟s and college discus to prepare the all matter for implementation of lesson study : contextual learning. The results of this study show that: a) the level of implementation of lesson study steps in The Teaching Practise in SDPN Setiabudi is very suitable to the monitoring stan-dard, level Plan, Do, and Se; b) The lesson study implementation can improve the activities of student in learning, so the student can improve the konowlegde and skill Keyword: Lesson Study, kontextual Learning, heat conduction.